Induction of Fetal Globin in β-Thalassemia: Cellular Obstacles and Molecular Progress - PERRINE, SUSAN P.; CASTANEDA, SERGUEI A.; BOOSALIS, MICHAEL S.; WHITE, GARY L.; JONES, BRANDON M.; BOHACEK, REGINE (Annals of the New York Academy of Sciences, 2005)
: Accelerated apoptosis of erythroid progenitors in β‐thalassemia is a significant barrier to definitive therapy because the beneficial effects of fetal globin‐inducing agents on globin chain balance may not be inducible in cells in which programmed cell death is established early. Accordingly, our objectives have been to identify methods to decrease cellular apoptosis and to identify orally tolerable fetal globin gene inducers. A pilot clinical trial was conducted to determine whether combined use of a fetal globin gene inducer (butyrate) and rhu‐erythropoietin (EPO), the hematopoietic growth factor that prolongs erythroid cell survival and stimulates erythroid proliferation, would produce additive hematologic responses in any thalassemia subjects. Butyrate and EPO were administered in 10 patients. Novel fetal globin gene inducers that also stimulate erythroid proliferation were evaluated for pharmacokinetic profiles. Patients with β+‐thalassemia had relatively low levels of endogenous EPO (<145 mU/mL) and had additive responses to administered EPO and butyrate. Patients with at least one β0‐globin mutation had higher baseline HbF levels (>60%) and EPO levels (>160 mU/mL), and three‐fourths of these subjects responded to the fetal globin gene inducer alone. A few select fetal globin‐inducing short‐chain fatty acid derivatives that stimulated cell proliferation also had favorable pharmacokinetics. These studies identify a significant subset of thalassemia patients who appear to require exogenous EPO to respond optimally to any HbF inducer, as well as new therapeutic candidates that act on both cellular and molecular pathologies of β‐thalassemia. Both approaches now offer excellent potential for tolerable, definitive treatment of β‐thalassemia.